Relationship between gas exchange parameters and first symptoms of Ulmus minor Mill. to Dutch elm disease - Solla, A.; Burón, M.; Gil, L. (Forest Systems, 2001)
Research has been carried out into the identification of easily measured anatomical or physiological parameters that are related to resistance, with the aim of screening elms resistant to Dutch elm disease. Given that the factors which encourage diffusion of this disease in elms also lead to an increase in symptoms, it is hypothesised that estomatic conductance (gs) and specific leaf hydraulic conductivity (CH) could be related to susceptibility. These parameters were determined in 75 U. minor seedlings, aged 7, 6, 3 and 2 years old (n . 15), which were subsequently inoculated with the Dutch elm disease fungus. In plants of 7, 6, and 3 years a positive relationship was observed between gs at 14 hours, and the amount of wilting shown after 15 days (r2 > 0,40; P * 0,01). This relationship was shown weaker with the amount of wilting after 60 days in 7 and 6 year old plants, whilst in 3 year old plants it became nonsignificant. Similar results were obtained between CH and the amount of wilting after 15 days in elms of 6 and 7 years. It is thought that the relationships observed occured because a greater gas exchange favours the colonisation or diffusion of the pathogen within the tree. The fact that neither gs nor CH showed relationships with susceptibility in two year old plants makes it inadvisable to use these parameters for the early screening of resistant U. minor trees.